A Study of optimum corn cob ratio in cement sand brick - Nur Hafizah, Mohd Shafee (2016)
This paper is an overview on the investigation of optimum corn cobs ratio in cement sand brick which gives the best properties of corn cob-cement sand brick (CCCSB) in terms of compressive strength, density and water absorption rate. The mix proportions cement:sand:corn cob used for this study were 1:5:1, 1:4.5:1.5 and 1:3:3. Every batching of mix proportions were measured by volume. A total of 90 CCCSB samples of size 225 mm x 113 mm x 75 mm were produced. For each mix proportion, 30 samples were prepared. There were 20 samples prepared for compression test, five samples prepared for density test and another five samples for water absorption test. The compression test results were taken at 3, 7, 14, and 28 days curing ages. The justification of choosing the optimum ratio of corn cobs inside the CCCSB were made based on the value of compressive strength, density, and water absorption rate obtained from compression test, density test and water absorption test respectively. The compressive strength of CCCSB is affected by corn cobs ratio inside it. This is due to the pozzolanic reaction which takes place after a few days inside the mixtures and increases with curing ages such that the strength of the mix proportion will increasing gradually. Meanwhile, the water absorption rate and the density are highly-related to each other which are also affected by the corn cobs ratio. The corn cob contains fibre which absorbs water excellently and is lightweight. When the corn cob ratio is high, the water absorption rate is also high as the increasing of pore spaces. This condition happened as the corn cobs will try to absorb the water and filling up the empty voids inside CCCSB. As the corn cob is considered as lightweight, the density of CCCSB will decrease as the corn cob ratio is increase. Therefore, based on the results, the optimum CC ratio in cement sand brick was ratio 1 from CCCSB mix proportion 1:5:1. This mix proportion has the highest compressive strength at 28 days which is 6.00 N/mm2 exceeding the Public Work Department (PWD) standard of minimum permissible average compressive strength of 5.2N/mm2 , the highest density which is 1650.84 kg/m3 and the lowest water absorption rate; 12.38% which falls under standard provided by ASTM C67 which is 20%.